Analisis Produksi dan Risiko Produksi Usahatani Cabai Rawit di Kecamatan Watunohu, Kabupaten Kolaka Utara - Muhtar Amin; Campina Illa Prihantini (Fakultas Pertanian, Universitas Timor, 2021)
This study aims to determine the factors that influence the production of cayenne pepper farming and the risks of cayenne pepper farming in Watunohu District, North Kolaka Regency. The number of respondents used in this study are 30 cayenne pepper farmers who were determined based on the snowballing sampling technique. The research method used was a field survey. Then, the survey results are used in linear regression analysis and risk analysis of chili farming using the SPSS application. The results of the study showed that there are three dependent variables that had a significant effect on the production of cayenne pepper. They are land area, seeds, and urea fertilizer. The risk of cayenne pepper farming in Watunohu District, North Kolaka Regency is in the low category as indicated by the coefficient of variance of 0.32. This means that in 100 times the production process, the chance of a production risk is 32 times the expected amount of cayenne pepper production.